2018
DOI: 10.1007/s00339-017-1541-x
|View full text |Cite
|
Sign up to set email alerts
|

2D materials in electro-optic modulation: energy efficiency, electrostatics, mode overlap, material transfer and integration

Abstract: Here we discuss the physics of electro-optic modulators deploying 2D materials. We include a scaling laws analysis showing how energy-efficiency and speed change for three underlying cavity systems as a function of critical device length scaling. A key result is that the energy-per-bit of the modulator is proportional to the volume of the device, thus making the case for submicron-scale modulators possible deploying a plasmonic optical mode. We then show how Graphene's Pauli-blocking modulation mechanism is se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This work focuses on charge-driven electro-absorption modulators (EAM) only, as opposed to electric field-driven designs, such as those based on Franz-Keldysh or Pockel's effect [15][16][17][18]. We mainly discuss three active materials only, namely silicon, indium-tin-oxide (ITO) and graphene, but briefly mention results regarding expected absorption of other two dimensional (2D) materials [19][20][21], quantum dots [22], and quantum wells [23,24]. The discussion thence includes a parametric study of achievable optical effective index changes as a function of the optical mode overlap factor with the active material, the materials own index change potential, and the effective mode's group index with bias.…”
Section: Electro-optic Modulator Challengesmentioning
confidence: 99%
“…This work focuses on charge-driven electro-absorption modulators (EAM) only, as opposed to electric field-driven designs, such as those based on Franz-Keldysh or Pockel's effect [15][16][17][18]. We mainly discuss three active materials only, namely silicon, indium-tin-oxide (ITO) and graphene, but briefly mention results regarding expected absorption of other two dimensional (2D) materials [19][20][21], quantum dots [22], and quantum wells [23,24]. The discussion thence includes a parametric study of achievable optical effective index changes as a function of the optical mode overlap factor with the active material, the materials own index change potential, and the effective mode's group index with bias.…”
Section: Electro-optic Modulator Challengesmentioning
confidence: 99%
“…Even if the latter still enables high-speed modulation it requires a great deal of additional power, therefore we believe that integration strategies aiming to minimize cross-talk and thermal effect, using for instance thermal polymers [63] would give a pathway for a high speed modulation using ring resonators without trading off energy consumption. However, we note that there are several emerging materials such as ITO and Graphene that are explored for efficient modulation [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], which include new modulation schemes and heterogeneous integration strategies, slow-light effects such as plasmon cavities. We now focus on the simulation of the architecture and its performance.…”
Section: Discussionmentioning
confidence: 99%
“…Electro‐optic modulators take advantage of electro‐optic effects to electrically modulate the light properties. [ 71,72 ] They actively work as the electric‐to‐optic conversion in the optical coupling that is one of the major parts within the integrated photonic circuits. [ 73 ] Phare et al.…”
Section: Electro‐optic Effect and Its Applications For 2d Materialsmentioning
confidence: 99%
“…Electro-optic modulators take advantage of electro-optic effects to electrically modulate the light properties. [71,72] They actively work as the electric-to-optic conversion in the optical coupling that is one of the major parts within the integrated photonic circuits. [73] Phare et al demonstrated an electro-optic modulator with greatly increased modulation speed and efficiency enabled by modulating the resonator loss at the critical coupling.…”
Section: Modulatorsmentioning
confidence: 99%